LITERARY STRUCTURE OF THE NOVEL "CINTA DI LANGIT QATAR" BASED ON PERSPECTIVE'S LUCIEN GOLDMAN - Wulandari, Betty Ayunda; Munawwarah, Madinatul; basid, Abdul (Annual International Conferences on Language, Literature, and Media, 2023)
The era of globalization clearly shows all aspects of development. One of them is the phenomenon of multiculturalism in creating a literary work. Cinta di Langit Qatar is one of the literary works influenced by multiculturalism, which is contained in the novel's structure. This study aims to show the form of the design of literary works in the novel Cinta di Langit Qatar by Defi Taslim based on Lucien Goldman's perspective and describe the form of the structure of literary works in the novel Cinta di Langit Qatar by Defi Taslim based on Lucien Goldman's perspective. This type of research is descriptive qualitative because the data analyzed are in the form of words or sentences by the study. Data collection techniques are reading techniques and note-taking techniques. Data analysis uses the Miles Huberman analysis model: reduction, presentation, and conclusion drawing. The data source used is primary data, the novel Cinta di Langit Qatar by Defi Taslim, supported by secondary data in the form of books and journal articles that support the research. The results of this study are the structural form of literary works in the novel "Cinta di Langit Qatar," namely intrinsic and extrinsic elements. Intrinsic elements include themes, namely Islamic Romance and persistence, four characters with different characters, points of view, mixed flow, setting, and mandate. In addition, this novel contains irrelevant elements in the form of social, religious, and the author's educational background.